Determination of Minimum Ecological Value of Wetland and Assessment of Hydrologic Alteration Indicators Affecting Local Communities’ Livelihood: Case Study Anzali Wetland (Journal of Global Humanities and Social Sciences, 2024)
Wetlands are of great importance to human society due to their direct and indirect delivery of goods and services; therefore, there has been a growing interest in the restoration and preservation of wetlands in different communities. To preserve the ecological values of wetlands and, thus, to ensure the local communities’ livelihood, it is essential to supply the water demand to provide ecological services relevant to the organisms in the ecosystems and also to the local communities around the wetland. A conceptual model derived from the integrated water resources management principles was used to assess the economic damages caused by the degradation of ecological conditions in Anzali Wetland. In order to quantify the assessment of this study, initially, the economic value of the entire wetland was estimated at 592,960 billion Iranian rials, which includes direct use value, indirect use value, and non-use value of about 28.5%, 10.5%, and 61%, respectively. Then, by defining the optimal and minimum acceptable conditions of Anzali Wetland in terms of ecological health, the economic value of wetland functions and services within the goals set for the livelihoods of local communities was obtained in the corresponding ecohydrological conditions. Finally, the value of wetland services was evaluated by comparing the current reduced economic value with both minimum and optimal ecological conditions. In this paper, by introducing the indicators for the vital wetland-related occupations, it was shown how disturbing the hydrological balance by impairing the tangible ecological services of Anzali Wetland influenced the IWRM, particularly the livelihoods of local communities in this system.